Dramatic vapor-phase modulation of the characteristics of graphene field-effect transistors. Issue 28 (28th July 2015) - Worley, Barrett C.; Kim, Seohee; Park, Saungeun; Rossky, Peter J.; Akinwande, Deji; Dodabalapur, Ananth
<x xml:space="preserve">Abstract</x> Graphene FETs exposed to vapor-phase, polar, organic molecules exhibit shifts in Dirac voltage, the magnitude of which obviously increase with increasing dipole moment of each type of polar vapor.